The Importance of Handling Early Childhood Who Experience Dyslexia Barriers - Feibry Senduk (CV. TOTUS TUUS, 2024)
This abdimasy activity has a goal, namely: (1) teachers can get to know early about the condition of their students who are suspected of experiencing developmental barriers (2 ) teachers will gain theoretical and practical scientific insights about handling early childhood children suspected of experiencing obstacles speech development (3) teachers can make early detection of the condition of their students who experience language development barriers. This activity took place at TK in April 20 22. Participants were followed by 20 teachers who came from several institutions. The training is conducted using discussion learning strategies / methods, brainstorming, drills, and assignments. The results of this service can be broken down into two, namely physical and physical nonphysical results. Non-physical results in the form of increasing knowledge and skills knowledge in handling early childhood children suffering from dyslexia. Physical results include devoted journal articles published in reputable national journal articles. The implementation of science and technology in the form of training activities on how to handle Aud children who have dyslexia for kindergarten teachers has been successful and successful. It is recommended, for Kindergarten teachers who have participated in the training can disseminate the knowledge and skills they have to other teachers around their assignments.